Magnesium in local edible ulam (Centella asiatica) and its relation to their habitat soils in Peninsular Malaysia - Ong, Ghim Hock; Yap, Chee Kong; Mahmood, Maziah; Tan, Soon Guan; Hamzah, Mohd Suhaimi (Universiti Putra Malaysia Press, 2017)
The aim of this study was to determine the Mg levels in Centella asiatica and their relationship to the habitat soils. Based on the levels of Mg in soils from the 12 sampling sites, its concentration was found to range from 13080 to 45350 µg/g dw. Although higher than the continental crust and European topsoils baselines, the soils of Peninsular Malaysia were considered 'unpolluted to moderately polluted' based on EF and 'deficiency to minimal enrichment' based on Igeo. As for plants, the highest Mg level was found in roots (3250 ± 815 µg/g dw), followed by leaves (2900 ± 565 µg/g dw) and stems (1660 ± 393 µg/g dw). This is in agreement with the transfer factor (TF). Based on correlation analysis and multiple linear regression analysis, Mg-Soil was found as a significant and the most important factor controlling the Mg uptake from the soils to the three plant parts. The direct relationships between Mg(plant)-Mg(Soil) also indicates that C. asiatica roots, leaves and stems are able to reflect the Mg levels of the sampling sites. Thus, the experimental transplantation studies under field and laboratory conditions confirmed the results from the field collected samples and indicated the roots, leaves and stems can be used as good biomonitors of Mg levels in the habitat soils.